A new species of Aricoris Westwood, 1851 (Lepidoptera: Riodinidae) from the Neotropical Cerrado savanna - Lemes, José R. A.; Callaghan, Curtis J.; Kaminski, Lucas A. (Zootaxa, 2020)
A new species of Aricoris Westwood, 1851, until now treated erroneously as Aricoris tutana (Godart, [1824]), is described and illustrated from the Neotropical Cerrado savanna. Aricoris emeryi Callaghan, Lemes & Kaminski, sp. nov. can be identified by a set of characters on wings and male genitalia that differentiates it from other species belonging to the constantius group.